The WTO Dispute Settlement System Issues on Implementation - Dewi, Yetty Komalasari (Indonesian Journal of International Law, 2008)
The dispute settlement body in the World Trade Organization (WTO) is the important element for the enforcement of rights and obligations to the party of the WTO. So, the implementation of the decision of the dispute settlement body greatly affects the existence of the WTO as a whole system. Regardless of the success of WTO in making a decision to the case between the parties, the certainty of execution of the awards is still not convinced many parties especially the winning member(s). This article will discuss about the reasons which cause the dispute settlement body awards cannot be executed. Besides, this article also analyzes the position of Indonesia against Korea in Korea Anti-Dumpuig Duties on Imports of Certain Paper from Indonesia case.